Effect of Addition Level of Turmeric Powder (Curcuma domestica) in Diet on Growth Performance of Crossbred Rabbit - Yusti Pujiawati; Ni Luh Gede Budiari; I Made Rai Yasa (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
The use of feed additive of turmeric powder aimed to improve the growth performances of rabbits. Conducted this research in the Riang Gede Village, Penebel District, Bali Province, in July-October 2018. The rabbit used were 20 aged 8-week-old male crossbred rabbits (New Zealand White and Local Rabbits). The design experimental used was a completely randomized design with four treatments and five replications with details of treatment, namely ration without turmeric powder (P0), ration with 0.5% turmeric powder (P1), ration with 1% turmeric powder (P2), ration with 1.5% turmeric powder (P3). The parameters observed were daily weight gain, final body weight, feed intake, and feed conversion ratio (FCR). Turmeric powder has a positive impact on feed intake, daily body weight gain, FCR, and final body weight of rabbits. The addition of 1.5% turmeric powder had the highest feed intake at first and third-month research 72.98 g/head/day and 106.26 g/head/day. The turmeric powder of 1.5% in ration had the greatest feed conversion ratio of 3.85 with a final body weight of 1902.2 g/head.